Pengaruh Edukasi Kesehatan terhadap Pengetahuan para Ibu Dusun Banjar Tengah dalam Deteksi Kanker Payudara Melalui SADARI - Farid, Nuril; Ageng Adhi Nugroho; Mutiara Ibna Nirmala; Sabila Rosyidah Wibawa Putri; Rifki Zidan Nugraha (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
This study aims to evaluate the effectiveness of early breast cancer detection counseling using the SADARI method in increasing the knowledge of the women participants in Dusun Banjar Tengah, as well as to identify the influencing factors.The activity was conducted in two sessions in March 2023. The first session consisted of an educational seminar using lectures and Power Point media, covering topics such as breast anatomy, cancer definition, risk factors, myths and facts, treatment, and prevention through SADARI. The second session included a initial clinical screening for women participants members experiencing complaints. Knowledge evaluation was carried out using pre-test and post-test assessments before and after the counseling. Data were analyzed quantitatively by comparing the average scores of the pre-test and post-test, and by analyzing the influence of age and education level on the score improvements. The results showed a significant increase in women participants knowledge scores after the counseling. Age and education level contributed to the improvement in knowledge scores. Early breast cancer detection counseling using the BSE method can significantly influence women participants knowledge. In addition, age and education are factors that affect the effectiveness of the counseling.